Analisis Peran Motivasi sebagai Mediasi Pengaruh Trilogi Kepemimpinan dan Kepuasan Kerja terhadap Produktivitas Kerja Karyawan PT. Mataram Tunggal Garment - Willis Gita Kinasis; Didik Subiyanto; Epsilandri Septyarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The purpose of this study is to find out the motivation to mediate the leadership trilogy and job satisfaction to employee work productivity at PT. Mataram Tunggal Garment. The method used in this study is quantitative. Primary data was obtained from questionnaires with 78 respondents with saturated sample techniques. Then the data is analyzed using descriptive analysis, multiple linear regression tests, t (partial) tests, coesifisien determination (R2) and sobel tests. The results showed that job satisfaction had a significant influence on motivation, leadership trilogy and job satisfaction had a significant influence on employee work productivity, leadership trilogy and motivation had no significant effect on employee work productivity, motivation mediated leadership trilogy and job satisfaction had no insignificant effect on employee work productivity. Keywords: Leadership Trilogy, Motivation, Job Satisfaction and Employee Productivity.